Predictors of Clinician Tobacco Intervention Counseling in Six North Carolina Free Clinics - John G. Spangler MD, MPH; Eun-Young Song PhD; Jessica Richardson Pockey MPH; Erin L. Sutfin PhD; Donald W. Helme PhD; Cindy Jones RCP; Kristie L. Foley PhD (SAGE Publishing, 2012)
While the poor and the uninsured are at increased risk for tobacco use, up to two thirds of these patients express interest in near-term quitting. Nonetheless, tobacco counseling rates remain low in clinics serving these patients. As part of a larger tobacco intervention project in North Carolina free clinics, we gathered baseline data on patient characteristics in six randomly selected facilities affiliated with the North Carolina Association of Free Clinics. An exit interview was completed by 231 patients; 126 (54%) were tobacco users. Among all patients, 71% had been asked by a clinician about tobacco use in the past 3 months. Among tobacco users, 68% had received at least one other counseling step (assessment; advice; or assistance). Patients with asthma and current tobacco users had a two-fold increase in being asked about tobacco use. Patients' diagnoses--in particular asthma--can remind clinicians of tobacco intervention.